Overconfidence and its link with feedback - Erat, Serhat; Demirkol, Kurtulus; Sallabas, M. Eyyup (SAGE PUBLICATIONS INC, 2022)
Feedback is crucial in every step of education, and we provide feedback to students in order to help them to either understand or improve their performance if they wish to improve their skills and abilities. However, how or whether they can benefit depends on their response to that feedback. Thus, when they receive feedback, they ought to be receptive because either too much or too little confidence influences their perceptions of their own performance. The study described in this article looks at overconfidence, and whether or not this evolves over time, that is, with more experience and also whether providing feedback to students can improve their own assessment of their own skills and abilities. A two-stage experiment was conducted, measuring the actual performance of students taking a course, at two points within it. After the examination that students took, we collected how students had assessed themselves and the degree of confidence that they had. Later, we provided feedback to students about their actual performance. In the second stage, we again measured their actual and self-estimated performance. The aim was to find out whether the feedback provided to students improved their assessment of their own performance and whether or not there had been a change in the level of their confidence. The results shed light on whether or not confidence, in particular, overconfidence, changes over time, in response to the feedback provided, and whether the provision of feedback is an effective policy when it comes to reducing overconfidence.
Keywords: feedback; judgment errors; self-image; student motivation; student performance; Education & Educational Research